La santé mentale des francophones et des anglophones vivant en situation minoritaire au Canada [infographie] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

Mental health status of Francophones and Anglophones living in minority situations in Canada [infographic] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

Suicide mortality gap between Francophones and Anglophones of Quebec, Canada - Burrows, Stephanie; Auger, Nathalie; Tamambang, Lum; Barry, Amadou. D. (Social psychiatry and psychiatric epidemiology, 2013)
Purpose Few studies evaluate language-group differences in suicide mortality. This study assessed the suicide mortality gap between Francophones and Anglophones of Quebec, Canada according to age, sex, method, region and socioeconomic deprivation. Methods Suicide decedents were extracted from the Quebec death file for 1989–2007 (N = 24,465). Age- and sex-specific suicide mortality rates were calculated for four periods (1989–1993, 1994–1998, 1999–2003, 2004–2007) for Francophones and Anglophones aged ≥10 years. Age-standardized rates of suicide by method, region, and level of social and material deprivation were calculated for each sex. Rate ratios and rate differences were estimated. Results Suicide rates for Francophones were two to three times higher than rates for Anglophones, and differences were greatest for adults aged 25–64 years. Francophone males had more than two times the rate of suicide by hanging or firearms than Anglophone males. Francophone females had twice the rate of hanging, poisoning or firearm suicide as Anglophone females, although precision was low. Francophone-Anglophone suicide mortality gaps were higher in urban areas despite lower suicide rates, and varied little across levels of social and material deprivation. Conclusions There was a large suicide mortality gap between Francophones and Anglophones of Quebec; especially, among adults aged 25–64 years.

Availability, accessibility and acceptability of english-language mental health services for the Estrie region’s english-speaking population: Service user and provider perspectives - Charpentier, Claude; Stout, Dale; Benoit, Annie; Poulin, Edith; Philip, Christopher (Journal of Eastern Townships Studies, 2011)
Mental illness affects about 1 in 5 Canadians during their lifetime but only approximately 30% of people needing help actually access mental health ser vices (Gravel, Connolly & Bédard, 2004). This low access rate is worrisome and may not accurately depict the reality as it is lived out by linguistic minorities. The present study documents both the need for and access to English-lan guage mental health services by the Estrie region’s English-speaking minority. Intending to record their needs and access experiences against the backdrop of available English-language mental health services, both users and providers of these services were surveyed in tandem. This novel approach to mental health needs assessment research shows the precarious situation of this minority community (high need/low access to language-congruent mental health ser vices) to be further compromised by misperceptions of service availability.

Do you speak English? Traitement sociopolitique de l’accessibilité aux services en santé mentale pour les anglophones du Québec - Kirouac, Laurie; Perreault, Isabelle (Minorités linguistiques et société, 2018)
À la fin des années 1970, le Québec se dote de la Charte de la langue française (Loi 101), qui modifie l’encadrement de la question de la langue de prestation des services de santé et de services sociaux. Parallèlement, de nombreux rapports, comités d’étude et politiques modifient en profondeur les pratiques institutionnelles et communautaires à l’endroit des personnes aux prises avec des problèmes de santé mentale. Depuis ce contexte de grandes transformations, où certaines réponses politiques ont été apportées aux préoccupations linguistiques, qu’en est-il de l’accès aux soins de santé mentale pour les anglophones du Québec ? Nous proposons de retracer dans ses grandes lignes l’évolution du traitement sociopolitique qui a été fait de la question de l’accessibilité des services en santé mentale pour les personnes anglophones en accordant une attention particulière à la situation montréalaise. Mots-clés : Québec, anglophones, santé mentale, minorité linguistique, services de santé

Official language minority communities in Canada: Is linguistic minority status a determinant of mental health? - Puchala, Chassidy; Leis, Anne; Lim, Hyun; Tempier, Raymond (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)

Access to health and social services for Quebec’s English-Speaking Minority Communities: Recent challenges, legislative context, and research recommendations. - Shoumarova, Lina (Quebec English-Speaking Communities Research Network, 2024)

Comparing the rates of mental disorders among different linguistic groups in a representative Canadian population - Vasiliadis, Helen-Maria; Lepnurm, Marje; Tempier, Raymond; Kovess-Masfety, Viviane (Social psychiatry and psychiatric epidemiology, 2012)
Purpose We aimed to determine whether linguistic group influences reported prevalence rates for a number of common mental disorders. Methods Secondary data analyses of the Canadian Community Health Survey cycle 1.2 (CCHS 1.2) were carried out on representative bilingual French and English, monolingual French and English and other language groups in Canada. Past year prevalence of major depression, anxiety disorders (agoraphobia, social phobia, panic disorder) and alcohol abuse/dependence were ascertained using versions of the World Mental Health Composite International Diagnostic Interview (WMH-CIDI) questionnaire. Multivariate data analyses were used to model past year presence of a mental disorder as a function of linguistic group, defined as languages can converse in, and adjusting for socioeconomic, demographic and cultural factors. Results Overall, past year rates for the presence of a common mental disorder were 10.7% (9.7–11.7%) for the bilingual English; 9.0% (8.1–9.9%) for the bilingual French; 10.2% (9.8–10.6) for the monolingual English; 8.5% (7.7–9.3%) for the monolingual French; and 8.3% (6.1–10.4%) for the other language group. After adjusting for a number of socio-demographic, economic and cultural factors, the multivariate analyses showed that the linguistic groups were equally likely to report the presence of a past year common mental disorder. This was also true for comparisons between the bilingual participants responding in French and English. Conclusions The differences observed in the reported crude rates for the presence of mental disorders across the different linguistic groups in Canada were explained by socio-demographic, economic, and factors such as immigration, spoke a third language and province of residence, and not explained by language of interview.